Gambaran Manajemen Sumber Daya Manusia Pada Layanan Kesehatan di Indonesia: Sebuah Literature Review - Fuadi, Mirza Fathan (Indonesian Journal of Health Community, 2025)
Human Resource Management (HRM) is a strategic component within the healthcare system that directly influences service quality and organizational performance. This review aims to identify and analyze literature discussing the roles, challenges, and strategies of HRM in the context of health services. The literature search was conducted through databases including PubMed, ScienceDirect, Directory of Open Access Journals (DOAJ), ResearchGate, Google Scholar, and Academia.edu using the keywords "human resource management", "health services", and "healthcare workforce" for articles published between 2019 and 2024. The findings highlight major HRM issues such as healthcare workforce shortages, excessive workloads, low staff retention, and suboptimal continuous training. Effective strategies identified include strengthening HR planning, capacity development, incentive-based approaches, and the use of information technology. These findings offer significant implications for policymakers and hospital managers in improving the effectiveness of healthcare workforce management. To address the key challenges in human resource management within healthcare services, it is recommended to implement need-based and data-driven workforce planning.